OBJETO DE APRENDIZAGEM: UM RECURSO EDUCACIONAL PARA O ENSINO DA MATEMÁTICA - SOARES, CARINE G. T.; PIVA, CLAUDIA; MICHAEL, DANIELI; GONÇALVES, MARCIA F.; EICKHOFF, FERNANDO (Salão do Conhecimento, 2013)
Resumo